Formal Reasoning and Self-Confidence, Their Influence on Students' Mathematical Problem-Solving Abilities - Damayanti, Nur Ismi; Misu, La; Anggo, Mustamin (Jurnal Amal Pendidikan, 2024)
Students' ability to solve mathematical problems is influenced by several factors, such as their reasoning approach to problems, which helps them understand and solve mathematical problems. Another factor is the level of self-confidence possessed by the students, which can motivate them to be more driven in solving mathematical problems. This study aims to examine the influence of formal reasoning and self-confidence on students' mathematical problem-solving abilities. The research design used is ex-post facto. The population and sample consist of 180 students. Data on formal reasoning and mathematical problem-solving ability were obtained through tests, while self-confidence data were collected using a questionnaire. The data analysis techniques used in this study are descriptive analysis and inferential analysis. Based on the results of the descriptive analysis and discussion, it was concluded that the majority of students' formal reasoning levels were in the proportional reasoning stage (61.1%), students' self-confidence was in the high category (34.1%), and students' mathematical problem-solving ability was in the low category (34.4%). The results of regression analysis concluded that there is a significant influence of formal reasoning and self-confidence on students' mathematical problem-solving abilities, both individually and jointly.